M-Learning in Developing Countries: Challenges, Remedies and Benefits in Instructional Activities - Olanrewaju, Olatayo Solomon; Ikuereye, Evbakoe Pedro (NIU Journal of Humanities; Vol 4 No 1 (2019): KIU Journal of Humanities, Vol. 4 No. 1, March 2019, 2019)
This paper attempted to discuss gains as well as weaknesses of m-learning usability in instructional activities in and outside classroom engagements. Hence, it examined its challenges, remedies and benefits in learning activities. Therefore, it is recommended that m-learning should be integrated into teaching and learning enterprise fully; teachers should be trained and retrained to develop maximum skills in Information and Communications Technology (ICT); and teachers should integrate and use m-learning in their classroom engagements. Keywords: M-learning, Technology, Information and Communications Technology, Challenges, Remedies